PENGEMBANGAN MEDIA KLIPING BEBASIS CANVA PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Resmita, Armi; Junaidi, Junaidi; Syafruddin, Syafruddin; Satrial, Ardi (Universitas Lampung, 2024)
One of the factors that influences the improvement of students' understanding and learning outcomes is the use and development of appropriate learning media by teachers, because the media functions as a tool to deliver teaching materials. Therefore, this study aims to evaluate the validity, practicality, and effectiveness of Canva-based clipping learning media for explanatory text material in grade 6 of elementary school. This study uses the R&D (Research and Development) method with the ADDIE (analysis, design, development, implementation, and evaluation) development model developed by Dick and Carry. The sources of information in this study involved validators and students as research subjects. The results of the development and trial of Canva-based clipping learning media show that this media is very valid overall, practical in its implementation and use, and effective in improving students' abilities in extracting information and presenting explanatory texts. The analysis data shows that student learning outcomes in the skills aspect reached 87.63 and the knowledge aspect reached 90.15. Thus, Canva-based clipping learning media can be a useful alternative for teachers in helping students who have difficulty in learning, especially in understanding and identifying text structures in Indonesian language lessons. Salah satu faktor yang mempengaruhi peningkatan pemahaman dan hasil belajar siswa adalah penggunaan serta pengembangan media pembelajaran yang sesuai oleh guru, karena media berfungsi sebagai alat untuk menyampaikan materi ajar. Oleh karena itu, penelitian ini bertujuan untuk mengevaluasi validitas, praktikalitas, dan efektivitas media pembelajaran kliping berbasis Canva untuk materi teks eksplanasi di kelas 6 SD. Penelitian ini menggunakan metode R&D (Research and Development) dengan model pengembangan ADDIE (analysis, design, development, implementation, and evaluation) yang dikembangkan oleh Dick dan Carry. Sumber informasi dalam penelitian ini melibatkan validator dan siswa sebagai subjek penelitian. Hasil pengembangan dan uji coba media pembelajaran kliping berbasis Canva menunjukkan bahwa media ini sangat valid secara keseluruhan, praktis dalam pelaksanaan dan penggunaannya, serta efektif dalam meningkatkan kemampuan siswa dalam mengekstraksi informasi dan menyajikan teks eksplanasi. Data analisis menunjukkan bahwa hasil belajar siswa dalam aspek keterampilan mencapai 87,63 dan aspek pengetahuan mencapai 90,15. Dengan demikian, media pembelajaran kliping berbasis Canva dapat menjadi alternatif yang berguna bagi guru dalam membantu siswa yang mengalami kesulitan dalam pembelajaran, khususnya dalam memahami dan mengidentifikasi struktur teks pada pelajaran bahasa Indonesia.